The Effect of Avicennia marina Leaf Extract Addition To the Artificial Feed On the Growth of Litopenaeus vannamei - Linayati - Linayati; Leonardus Bayu Nugroho; Tri Yusufi Mardiana; Hayati Soeprapto; Muhammad Zulkham Yahya (Departemen Akuakultur FPIK UNDIP, 2023)
Mangrove leaves contain abundant bioactive compounds that can optimize the growth of shrimp. This research examined the effect of adding Avicennia marina leaves to feed on the growth and FCR of Whiteleg shrimp and determined the optimal dose. Whiteleg shrimp seeds of PL-20 were used in experiments that employed RAL method with 4 treatments and 3 replications. Different doses of Avicennia marina leaf extract were used: (A) 125 ppm/500 g feed, (B) 175 ppm/500 g feed, (C) 225 ppm/500 g feed (D). The feed amounted to 3% of the total biomass per treatment every day administered in 5 meals daily for 30 days. The most optimal dose for the growth of shrimp was 225 ppm/500 g (D) with an absolute growth of 7.71 g and FCR of 1.27. However, the treatment did not affect the SR of shrimp for its value reached 100% in all treatments. The parameters of water quality were temperature of 27.4–30⁰C, DO 6.3 – 7.9, salinity 13–15 ppt, and pH 7.5 – 7.8. Keywords: Avicennia marina, Growth, Litopenaeus vannamei